Pengaruh Permainan Kooperatif Terhadap Peningkatan Interaksi Sosial Anak Usia 5-6 Tahun di TK Pembina HKBP Tarutung - Agus Niada Lawolo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study was to determine the effect of cooperative games on improving social interaction among 5-6 year old children at the Pembina HKBP Tarutung Kindergarten. The research hypothesis was: "cooperative game activities affect the improvement of social interaction among 5-6 year old children at the Pembina HKBP Tarutung Kindergarten." The population consisted of 70 children aged 5-6 years (group B) enrolled at Pembina HKBP Tarutung Kindergarten. The research sample was determined using purposive sampling technique, namely the Angkasa, Bintang, and Bulan classes were designated as the experimental group consisting of 37 children, while the Jupiter, Matahari, and Pelangi classes were designated as the control group consisting of 33 children. The research method used was quantitative research with a quasi-experimental method and a Nonequivalent Control Group Design. The instrument used in this study was a questionnaire consisting of 17 items. The research data for the questionnaire was analyzed using the mean difference test formula (N-Gain Score). The mean value for the experimental class was 0.7330, which was in the high category. The mean value for the control class was 0.1493, which was in the low category. From the results of the research conducted, an independent test was then performed using the t-test and obtained a t-count value = 14.155 > t table (α=0.05; df=68) = 1.667. Thus, it can be concluded that the research hypothesis (Ha) is accepted, namely that cooperative play activities influence the increase in social interaction among 5-6 year olds at the Pembina HKBP Tarutung Kindergarten, and H0 is rejected.